FENOMENOLOGI MUSIK - Sigit Djatmiko (Pascasarjana Universitas Hindu Indonesia, 2016)
The Kraftwerk music group from Dusseldorf, Germany, began to be famous since 1974. The prominent feature of the Kraftwerk is that they were trying to be the pioneer of the alteration from the acoustic and electric music into the electronic music. Their mission was dehumanizing the music to produce impersonal sounds and with the â€œmusiciansâ€ which would rather be considered as machine tools than as human. The works of the Kraftwerk arguably became the blueprint for the sort of avantgarde music, the prototype for kinds of music that celebrated the shift from the sounds of the guitar strings and the human vocal into the sounds of strum combination. In sum, the main aim of the Kraftwerk was to fully merge with the technology, to stop playing the instruments, and let the instruments play themselves.